CECOS: a Centralized Management Platform Supported by Distributed Services to Represent and Manage Resources Aggregation Entities and its End-users in a Smart Grid Context. Issue 9 (2022) - Pereira, Helder; Ribeiro, Bruno; Gomes, Luís; Vale, Zita
Abstract: The evolution of the smart grid and its benefits for energy players drives changes in the behaviour of all the parties involved in the power and energy systems. Thus, the existence of platforms to manage participation in aggregation entities and services gains importance, as they help to monitor players' energy resources, and make their management more intuitive. This paper proposes an upgrade to the platform CECOS, initially designed to manage energy communities and their members. With the upgrade, the platform manages the players and entities belonging to the smart grid. The new version of the platform is not limited to its original services, as it allows the registration of distributed services, such as demand response, or forecast, by service providers. Furthermore, it allows the participation in several aggregation entities simultaneously, and provides a mobility mechanism, to allow players to move among entities to achieve their goals. A case study was developed to evaluate the platform, considering different types of forecasts and demonstrating favourable outcomes in terms of the predictions' error decrease.